Dimensional personality pathology and disordered eating in young adults: measuring the DSM-5 alternative model using the PID-5 - Gilmartin, Tanya Louise; Gurvich, Caroline; Dipnall, Joanna F.; Sharp, Gemma (Frontiers in Psychology, 2023)
Introduction The Personality Inventory for DSM-5 (PID-5) is a self-report measure of personality pathology designed to measure pathological personality traits outlined in the DSM-5 alternative model of personality disorders. Within the extensive literature exploring the relationship between personality and disordered eating, there are few that explore the relationship between the PID-5 and disordered eating behaviours in a non-clinical sample of males and females: restrictive eating, binge eating, purging, chewing and spitting, excessive exercising and muscle building. Methods An online survey assessed disordered eating, PID-5 traits and general psychopathology and was completed by 394 female and 167 male participants aged 16–30. Simultaneous equations path models were systematically generated for each disordered eating behaviour to identify how the PID-5 scales, body dissatisfaction and age predicted behaviour. Results The results indicated that each of the six disordered behaviours were associated with a unique pattern of maladaptive personality traits. The statistical models differed between males and females indicating possible differences in how dimensional personality pathology and disordered eating relate. Discussion It was concluded that understanding disordered eating behaviour in the context of personality pathology may assist formulating potentially risky behaviour.